Attitudes of community health agents against alcoholism and alcoholists (Research, Society and Development, 2020)
This study aimed to analyze the attitudes of Community Health Agents towards alcohol, alcoholism, and people with disorders related to alcohol use. Descriptive exploratory study, with psychometric approach, performed with 129 community health agents from the city of Jequié, Bahia, Brazil. For the production of the data, we used the Attitudes Scale against alcohol, alcoholism and people with disorders related to alcohol use and a questionnaire containing sociodemographic and work information. In the statistical analysis, tools of descriptive statistics were used, and Pearson's Chi-square test was used for association tests. Most of the respondents were female (91.5%), (69.9%) with complete secondary education, (86%) reported having had experience with alcoholics while working. Attitudes throughout the scale were negative (3,13), but within the factors that make up the scale, the only one that had positive attitudes was work-related and interpersonal relationships with the alcoholic (3,39). Negative attitudes of the participants, in the whole instrument used, can be attributed to the lack of preparation before entering the health service or ineffective preparation. Public policies and educational campaigns are needed to modify this reality of the studied population.